2017
DOI: 10.1177/1756283x17710247
|View full text |Cite
|
Sign up to set email alerts
|

Noncirrhotic hepatocellular carcinoma: etiology and occult hepatitis B virus infection in a hepatitis B virus-endemic area

Abstract: Background:Although hepatocellular carcinoma (HCC) usually develops in cirrhotic livers, a minority of cases occur in noncirrhotic livers (NCLs). We investigated etiology, clinicopathological features, and occult hepatitis B virus (HBV) infection (OBI) in patients with NCL HCC in an HBV-endemic area.Methods:A total of 710 patients who underwent resection or transplantation for HCC at the National Cancer Center (NCC), Korea, were enrolled. HCC and fibrosis stage were diagnosed pathologically.Results:A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 23 publications
1
37
0
Order By: Relevance
“…Since Korea is a HBV-endemic area, prior HBV infection is considered to play a role even in the development of cryptogenic HCC [ 22 ]. A recent study reported that 82.1% of patients were positive for anti-HBc in serum and 52.6% were positive for both anti-HBc in serum and HBV DNA in the liver tissue among 78 patients who underwent resection or transplantation for cryptogenic HCC [ 23 ].…”
Section: Etiology Of Hcc In Koreamentioning
confidence: 99%
See 2 more Smart Citations
“…Since Korea is a HBV-endemic area, prior HBV infection is considered to play a role even in the development of cryptogenic HCC [ 22 ]. A recent study reported that 82.1% of patients were positive for anti-HBc in serum and 52.6% were positive for both anti-HBc in serum and HBV DNA in the liver tissue among 78 patients who underwent resection or transplantation for cryptogenic HCC [ 23 ].…”
Section: Etiology Of Hcc In Koreamentioning
confidence: 99%
“…The prevalence of diabetes and obesity is increasing, and the age-standardized prevalences of diabetes and obesity (body mass index of 25 kg/m 2 or higher) in Korean adults were 11.0% and 31.8%, respectively [ 24 ]. Recent studies reported that diabetes was found in 21.8–37.1% of Korean patients with cryptogenic HCC [ 11 , 23 ]. It is of concern that nonalcoholic fatty liver disease-associated HCC can also develop in a non-cirrhotic liver [ 23 ].…”
Section: Etiology Of Hcc In Koreamentioning
confidence: 99%
See 1 more Smart Citation
“…This situation implies that a significant fraction of Peruvian patients would have cryptogenic HCC, which is commonly characterized by a well-conserved architecture of the liver parenchyma and absence of a bona fide risk factor, such as overt HBV or HCV infections. It has been previously reported that occult HBV infection (OBI), defined by the presence of HBV DNA in blood or liver tissue without detectable levels of HBsAg, can be associated with non-cirrhotic HCC 44 . This is why we undertook a comprehensive molecular detection of HBV in tumor and non-tumor liver tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of HCC in HCV-infected individuals without cirrhosis has a prevalence of 16% to 30%. 43 , 44 The likelihood of HCC development in patients without advanced fibrosis may suggest the presence of other components in the pathological process of HCV that are not yet understood. 44 Several studies have documented a significant risk reduction for HCC when patients achieved sustained viral clearance with interferon treatment.…”
Section: Discussionmentioning
confidence: 99%